Michael Wolff , Fire and Fury inside the Trump White House, Estados Unidos, Editorial Henry Hold and Company, 2018, 312. - Rayes El Kantar, Ángel Rabih (MUUCH' XÍIMBAL CAMINEMOS JUNTOS, 2018)
Reseña de Michael Wolff , Fire and Fury inside the Trump White House, Estados Unidos, Editorial Henry Hold and Company, 2018, 312.